Kepatuhan Wajib Pajak: Studi Pada UMKM Gerabah di Desa Wisata Kasongan - Cristin Susilowati; Rochmad Bayu Utomo (Universitas Muhammadiyah Palembang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy, including Kasongan Yogyakarta. However, tax compliance remains low, with 89.19 percent of business owners not having Taxpayer Identification Number (NPWP). This study analyses the influence of perceptions of tax fairness and trust in the government on tax compliance, with tax payment motivation as a mediating variable. The sample consisted of 60 MSMEs actors in Kasongan Tourism Villageselected through purposive sampling. Data were collected using questionnaires and analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM). The results show trust in the government and tax payment motivation positively and significantly influenced tax compliance, while tax fairness perceptions had no significant effect. Tax payment motivation does not mediate the relationship between perceptions of fairness and compliance, highlighting the importance of transparency and trust in improving MSME tax compliance.